The Relationship Between Christianity and Science: A Brief Historical Study on Darwinism and the Old Princeton Theologians - David Tong (Societas Dei: Jurnal Agama dan Masyarakat, 2014)
Abstract: Richard Dawkins openly declares that he is strongly against religion since religion destroys scientific works. This assumption is not something new. Since the end of the 19th century there was a development of a thesis that claims Christianity and science are two antagonistic poles. Although this thesis is now inadequate, many Christians are still holding on to this view. In realty, the development of Darwinism in the United States is also supported by Christian scientists. When we study Old Princeton theologians we find that they have different attitude about science. When they face pressure on the development of science (in this case evolution), they actually are not reticent in accepting the fact of evolution although they reject mechanistic and naturalistic interpretation of Darwinism upon those facts. Old Princeton theologians give examples on how Christian should take a stand on science. Evangelicals in Indonesia can learn a lot of from their history and tradition. KEYWORDS: Charles Hodge, Archibald Alexander Hodge, Benjamin Breckinridge Warfiled, John Gresham Machen, Old Princeton, evolution, theistic evolution, Darwinism